2023
DOI: 10.1021/acs.jpcc.3c03856
|View full text |Cite
|
Sign up to set email alerts
|

Interband- and Intraband-Induced Hot Electron Transfer in Plasmonic Gold–Cerium Oxide Core–Shell Nanoparticles

Supriya Ghosh,
Bach Pham,
Meera Madhu
et al.

Abstract: The high optical cross sections of plasmonic nanoparticles make them attractive for applications in photovoltaics and photocatalysis that seek to convert light into electrical charges. However, the ultrafast deactivation of hot electrons via electron–electron scattering has limited their utilization. Here, we describe hot electron transfer (HET) in core–shell nanoparticles with a gold core and a cerium oxide (CeO2) shell and in a three-component hierarchical material in which the core–shell nanoparticles are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Spurio et al use thin-film ceria deposited on an array of gold nanoparticles 29 while Ghosh et al use gold–ceria core–shell nanoparticles. 30 In either case, exciting the gold nanoparticles with visible light populates the ceria 4f band, but with no evidence of promotion to the conduction band. As shown by Ghosh et al , photocatalytic behavior is still readily observed; conduction band electrons are not required to drive chemistry.…”
Section: Optical Properties Of Ceo2mentioning
confidence: 97%
“…Spurio et al use thin-film ceria deposited on an array of gold nanoparticles 29 while Ghosh et al use gold–ceria core–shell nanoparticles. 30 In either case, exciting the gold nanoparticles with visible light populates the ceria 4f band, but with no evidence of promotion to the conduction band. As shown by Ghosh et al , photocatalytic behavior is still readily observed; conduction band electrons are not required to drive chemistry.…”
Section: Optical Properties Of Ceo2mentioning
confidence: 97%